POST PARTUM DEPRESSION AMONG WOMEN BANKERS AND TRADERS IN EKITI STATE NIGERIA - Samuel Olutunde, Olatunji (IJRDO - Journal of Social Science and Humanities Research, 2017)
Postpartum depression is an unusual and frequently undocumented issue that impacts negatively on women and their children. The study was carried out among women bankers and traders in Ado Ekiti, Ekiti State, Nigeria. A cross-sectional study was conducted using a random selection technique. A total of 150 participants (60 bankers and 90 women traders) were randomly selected from 10 banks and two markets respectively. The participants selected age range between 18 and 58 years (mean age of 38.77). The instruments employed for data collection was a structured self- administered questionnaire developed by Aaron Beck (Beck Depression Inventory (BDI)) with 21 -items and the socio-demographic questions developed by the first author. The result revealed that bankers in Ado Ekiti experienced more postpartum depression than traders (t (148) = 6.34, p<.05). Findings were discussed in the light of existing literature.